Application of enzymes in the preparation of wheat germ polypeptides and their biological activities - Du, Ke; Tian, Shuangqi; Chen, Hu; Gao, Sensen; Dong, Xianyou; Yan, Feng (Frontiers in Nutrition, 2022)
Wheat germ, a byproduct of wheat industrial processing, contains 30% protein and is a comprehensive source of plant-based protein. But a large amount of wheat germs are disposed of as waste every year. Wheat germ protein can be hydrolyzed into polypeptides with antioxidant, antihypertensive, anti-tumor, bacteriostatic and other activities. At present, researches on the hydrolysis of wheat germ protein and the preparation of bioactive peptides from wheat germ protein have attracted increasing attentions. However, the traditional protein hydrolysis method, protease hydrolysis, can no longer meet the market’s needs for efficient production. Various auxiliary means, such as ultrasound, microwave and membrane separation, were applied to boost the yield and biological activity of wheat germ peptides by enzymatic hydrolysis. Under ultrasound and microwave, the protein structure may expand to increase the binding sites between enzyme and substrate and promote hydrolysis efficiency. Membrane separation is applied to separate products from enzymatic hydrolysate to reduce the inhibitory effect of the product on the hydrolysis reaction. The paper reviewed the hydrolysis methods of wheat germ protein and summarized the biological activity of wheat germ peptides to provide references for further study of wheat germ peptides.